2015
DOI: 10.1111/scs.12259
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of nursing studies in diabetes research published over three decades in Sweden, Norway, Denmark and Iceland: a narrative review of the literature

Abstract: Similarities and differences across borders of Nordic countries constitute a suitable context for investigating and discussing factors related to the development of diabetes nursing research over the last three decades. The present study reviewed the entire body of contemporary diabetes nursing research literature originating in four Nordic countries: Norway, Sweden, Denmark and Iceland. Our aims were (i) to catalogue and characterise trends in research designs and research areas of these studies published ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…This finding is similar to reviews conducted in other countries and regions, where most nursing research was either qualitative or consisted of cross-sectional and descriptive designs (Iversen et al, 2016; Khalaf, 2013; Sun & Larson, 2015). In addition, the focus on chronic diseases is reflective of a focus on the growing issue of “lifestyle” diseases.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This finding is similar to reviews conducted in other countries and regions, where most nursing research was either qualitative or consisted of cross-sectional and descriptive designs (Iversen et al, 2016; Khalaf, 2013; Sun & Larson, 2015). In addition, the focus on chronic diseases is reflective of a focus on the growing issue of “lifestyle” diseases.…”
Section: Discussionsupporting
confidence: 84%
“…To understand the state of the science of nurse-led or midwife-led clinical research, systematic and scoping reviews have been conducted in numerous countries and regions. For example, researchers have assessed the status and scope of nursing research in the United Kingdom (Rafferty, 2000), Australia (Borbasi, Hawes, Wilkes, Stewart, & May, 2002), Turkey (Ozsoy, 2007), Germany and the European Context (Hackmann, 2000), Jordan (Khalaf, 2013), nursing research related to diabetes in Nordic countries (Iversen et al, 2016), and in all of the African countries (Sun & Larson, 2015). These studies highlighted various levels of progress, development, and influence of nursing and midwifery research on health in their respective locations.…”
Section: Introductionmentioning
confidence: 99%
“…This comprehensive and humanized approach to care seeks to improve the patient's knowledge regarding the pathology, which connects them with their treatment and allows them to assume autonomous responsibility for their health 21 . Furthermore, numerous recent meta-analyses have shown that nurse-led interventions can enhance diabetes outcomes [22][23][24][25][26] . Nevertheless, there is no clear international evidence regarding the effectiveness of home visit programs for diabetes management, despite their promising results for other conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke (Lightbody, ; Rowat et al, ), heart failure (Stamp et al, ), Parkinson's disease (Shin & Habermann, ), osteoarthritis (Robbins & Kulesa, ), diabetes (Graue et al, ; Iversen et al, ) and stoma (Hubbard et al, ) are considered to be the above‐mentioned areas of diseases. With respect to nursing research on diabetes, Iversen et al () believe that future research may benefit from larger nurse‐led research programmes organized into networks to share knowledge and expertise across national groups. Autism and developmental disabilities are regarded as specific fields where additional nursing research should be conducted (Tomlinson et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The third domain encompasses diseases where nursing research is scarce, and as a result, more research is urgently called for. Stroke (Lightbody, 2017;Rowat et al, 2016), heart failure (Stamp et al, 2018), Parkinson's disease (Shin & Habermann, 2016), osteoarthritis (Robbins & Kulesa, 2012), diabetes (Graue et al, 2013;Iversen et al, 2016) and stoma (Hubbard et al, 2017) are considered to be the above-mentioned areas of diseases. With respect to nursing research on diabetes, Iversen et al (2016) believe that future research may benefit from larger nurse-led research programmes organized into networks to share knowledge and expertise across national groups.…”
Section: Diseases and Specific Fields From The Nursing Perspectivementioning
confidence: 99%